2008
DOI: 10.1016/j.bbrc.2008.09.043
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans mitochondrial K+ATP channel: A potential target for preconditioning

Abstract: Ischemic preconditioning (IPC) is an evolutionarily conserved endogenous mechanism whereby short periods of non-lethal exposure to hypoxia alleviate damage caused by subsequent ischemia reperfusion (IR). Pharmacologic targeting has suggested that the mitochondrial ATP-sensitive potassium channel (mK ATP ) is central to IPC signaling, despite its lack of molecular identity. Here, we report that isolated Caenorhabditis elegans mitochondria have a mK ATP channel with the same physiologic and pharmacologic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
1
32
1
Order By: Relevance
“…The pharmacology of mitoK ATP is conserved in humans [137], rats [79], plants [138], amoeba [139], trypanosomes [140], and C. elegans [141], and remains the default method to assign a role for mitoK ATP in IR protection. A catalog of K + channel pharmacophores applicable to mitochondrial research is given in Table 1.…”
Section: Mitochondrial Katp Channel: Composition Pharmacology Regulmentioning
confidence: 99%
“…The pharmacology of mitoK ATP is conserved in humans [137], rats [79], plants [138], amoeba [139], trypanosomes [140], and C. elegans [141], and remains the default method to assign a role for mitoK ATP in IR protection. A catalog of K + channel pharmacophores applicable to mitochondrial research is given in Table 1.…”
Section: Mitochondrial Katp Channel: Composition Pharmacology Regulmentioning
confidence: 99%
“…MitoK ATP activity was identified also in mitochondria of the nematode worm Caenorhabditis elegans [194]. Furthermore, in plant mitochondria, which possess a very active K + cycle, a K + uniport pathway with characteristics of mitoKATP has been observed to sustain an ion flow sufficient to uncouple respiration [38, 95,141,142].…”
Section: The Mitochondrial Atp-dependent Potassium Channelmentioning
confidence: 99%
“…Our own work has shown that worm mitochondria, like those from mammals, have both K ATP and big conductance potassium (BK) channels whose activities appear to be both necessary and sufficient for protection from ischemic damage (Wojtovich et al, 2008). Interestingly, metabolic profiling in worms with Ox-Phos mutations suggests a transition to alternate means of ATP production that do not require O 2 , and these worms are both long-lived and resistant to ischemia (Butler et al, 2010; Rea et al, 2007).…”
Section: Current Researchmentioning
confidence: 99%